Genome-wide analysis of the Populus trichocarpa laccase gene family and functional identification of PtrLAC23 - Liao, Boyang; Wang, Chencan; Li, Xiaoxu; Man, Yi; Ruan, Hang; Zhao, Yuanyuan (Frontiers in Plant Science, 2023)
Introduction Biofuel is a kind of sustainable, renewable and environment friendly energy. Lignocellulose from the stems of woody plants is the main raw material for “second generation biofuels”. Lignin content limits fermentation yield and is therefore a major obstacle in biofuel production. Plant laccase plays an important role in the final step of lignin formation, which provides a new strategy for us to obtain ideal biofuels by regulating the expression of laccase genes to directly gain the desired lignin content or change the composition of lignin. Methods Multiple sequence alignment and phylogenetic analysis were used to classify PtrLAC genes; sequence features of PtrLACs were revealed by gene structure and motif composition analysis; gene duplication, interspecific collinearity and Ka/Ks analysis were conducted to identify ancient PtrLACs; expression levels of PtrLAC genes were measured by RNA-Seq data and qRT-PCR; domain analysis combine with cis-acting elements prediction together showed the potential function of PtrLACs. Furthermore, Alphafold2 was used to simulate laccase 3D structures, proLAC23::LAC23-eGFP transgenic Populus stem transects were applied to fluorescence observation. Results A comprehensive analysis of the P. trichocarpa laccase gene (PtLAC) family was performed. Some ancient PtrLAC genes such as PtrLAC25, PtrLAC19 and PtrLAC41 were identified. Gene structure and distribution of conserved motifs clearly showed sequence characteristics of each PtrLAC. Combining published RNA-Seq data and qRT-PCR analysis, we revealed the expression pattern of PtrLAC gene family. Prediction results of cis-acting elements show that PtrLAC gene regulation was closely related to light. Through above analyses, we selected 5 laccases and used Alphafold2 to simulate protein 3D structures, results showed that PtrLAC23 may be closely related to the lignification. Fluorescence observation of proLAC23::LAC23-eGFP transgenic Populus stem transects and qRT-PCR results confirmed our hypothesis again. Discussion In this study, we fully analyzed the Populus trichocarpa laccase gene family and identified key laccase genes related to lignification. These findings not only provide new insights into the characteristics and functions of Populus laccase, but also give a new understanding of the broad prospects of plant laccase in lignocellulosic biofuel production.